An observational study on diagnosis index of metabolic disease with blood-stasis. Issue 27 (2nd July 2020) - Ko, Mi Mi; Jang, Soobin; Jung, Jeeyoun
Abstract: Introduction: Treating blood stasis is effective in treating obesity and metabolic diseases in traditional Korean medicine. The aim of this prospective observational study is to determine the effectiveness of the diagnosis index for metabolic diseases with blood stasis by analyzing clinical data and blood samples. Methods and analysis: We will perform a prospective observational study. Participants who meet the inclusion criteria will be recruited from the Dongguk university Ilsan Oriental hospital. The outcomes are resistin, serum amyloid P component, C-reactive protein, D-dimer, and blood stasis scores. In addition, the blood pressure, ankle–brachial pressure index, brachial–ankle pulse wave velocity, body mass index, waist circumference, and levels of blood lipid will be assessed. Discussion: Through this study, we could collect specific data for diagnosing metabolic diseases with blood stasis. Therefore, the findings of this study will provide a summary of the current state of evidence regarding the effectiveness of the diagnosis index in managing metabolic disease with blood stasis. Ethics and dissemination: The study was approved by the Institutional Review Board of the Dongguk University Ilsan Oriental Hospital (DUIOH-2018-09-001-007). The results will be published in a peer-reviewed journal and will be disseminated electronically and in print. Trial registration number: Clinical Research Information Service: KCT0003548 Abstract : Supplemental Digital Content is available in the text